Research on the Application of Computer-based Psychotherapy in Clinical Guidance - Ai, Yingtong; Zhang, Liwen; Zhang, Dawei (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Based on the B/S architecture combined with MVC programming ideas, this paper uses Python language to design and implement a computer psychotherapy system. Numerous experimental results show that its effect is not significantly different from traditional therapies, and it has broad prospects for development.